Fire Risk of Electric Bicycle Based on Fuzzy Bayesian Network. (July 2020) - Li, Ying; Han, Lei; Ning, Xiuli; Xu, Yingcheng
Abstract: Frequent fire incidents on electric bicycles; have brought great harm to consumers' personal and property safety. This article sort and analyze the data, combine the collected accident reports of electric bicycles. Due to the incompleteness of the data, this article use Bayesian Network to construct the Bayesian network topology model of electric bicycles fire risk, use fuzzy set theory to solve Fuzzy computing the language discussed by experts. Finally, the fuzzy Bayesian theory is used to calculate the example, and the fire risk of the electric bicycle in the example is low. This method provides a reference for the accident investigation and analysis of electric bicycles.